Deepening Problems of Domestic Workers During the COVID-19 Outbreak: The Case of Istanbul - Ceyhun Güler (Journal of Economy Culture and Society)
The COVID-19 outbreak has caused social and economic problems at a global level. Unemployment, reduced participation in the workforce, loss of income, lack of social protection, and infection are among employment-related problems, impacting insecure groups, mostly working informally adversely. Domestic workers included in these groups were particularly vulnerable during the pandemic due to informality and insecurity. This study aims to understand the issues faced by 35women domestic workers in Istanbul throughout the pandemic by conducting in-depth interviews using semi-structured questions via online platforms or phone calls. The problems and rights violations experienced by domestic workers were evaluated descriptively through interview data within the study’s scope. Research findings show that domestic workers are subjected to numerous rights violations related to the right to work and other fundamental human rights. Among the issues raised in interviews, loss of work and income, lack of social protection, heavy workload, and inability to access paid leave emerged.